Suitability of treated wastewater with respect to pH, electrical conductivity, selected cations and sodium adsorption ratio for irrigation in a semi-arid region - Mashela, Phatu W; Manyevere, Alen; Kgopa, Pholosho M (Water South Africa, 2018)
Increasing incidents of drought spells in most Sub-Saharan African countries call for exploration of innovative alternative sources of water for irrigation. A study was conducted to investigate the cation concentrations for different disposal points of treated wastewater and for borehole water. A 4 × 5 factorial experiment included a borehole as a reference sampling site plus three other sampling sites along the wastewater disposal system over 5 months. Monthly collected water samples were analysed for pH, EC, Ca, Mg, Na and K, with sodium adsorption ratio (SAR) computed and compared with those of water from the borehole, the FAO-desired ranges and the South African (SA) quality standards for irrigation water. Except at two sampling sites during one month, pH values were within the FAO-desired range. Relative to the FAO desired ranges and SA water quality standards, most variables in treated wastewater were much lower, suggesting that the test treated wastewater was suitable for irrigation.
Article published in the Water South Africa Vol. 44 No. 4 October 2018
Keywords: Cation content; Temporal effects; Treated wastewater disposal; Water scarcity; Plant-water relationships -- South Africa